The Influence of Sustainability Performance and Institutional Ownership on Earnings Management In ASEAN Countries - Danti Sagita; Inten Meutia; Hasni Yusrianti (Owner : Riset dan Jurnal Akuntansi, 2026)
This research is prompted by the escalating emphasis on sustainability performance and corporate governance across the ASEAN countries, along with persistent concerns regarding financial reporting manipulation that weakens the credibility and reliability of corporate disclosures. This study adopts a quantitative approach using secondary data from 238 non-financial sector firms in ASEAN (Indonesia, Malaysia, Singapore, and Thailand) over the 2016–2023 period. Data analysis was performed using panel data regression with the Fixed Effect Model (FEM), implemented through EViews version 12. The results indicate that sustainability performance does not exert a significant influence on earnings management, suggesting that sustainability initiatives in the ASEAN countries remain predominantly symbolic and have not yet functioned effectively as managerial monitoring mechanisms. In contrast, institutional ownership demonstrates a significant negative effect on earnings management, implying that higher levels of institutional shareholding are associated with reduced earnings manipulation levels. Regarding the control variables, firm size and leverage show significant negative effects on earnings management, whereas profitability and industry type show no significant impact. Overall, the findings imply that internal corporate attributes, particularly ownership structure and governance mechanisms, play a more substantial role than external factors in constraining managerial opportunism. This study provides important implications for managers, investors, and regulators across ASEAN countries to strengthen the corporate governance frameworks and encourage more substantive sustainability practices, enabling them to function not merely as compliance instruments but also as mechanisms for enhancing transparency and the integrity of financial reporting.